"R" for revenge - William, Kate.; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam, 1997)
Cheerleading co-captains Jessica Wakefield and Heather Mallone thought they'd found the perfect faculty advisor for their squad in Nancy Swanson. They were sure the mousy assistant librarian wouldn't cramp their style at all. But neither of them knows about the dark secret in Nancy's past, or how dangerous she really is.
Keywords: Twins -- Fiction; Revenge -- Fiction; Detective and mystery stories; Cheerleading -- Fiction; Librarians -- Fiction; Mystery and detective stories